Is Malaysian Fish Export Competitive Compared with that of other Asean Countries? - Hui Soh, Bee; Ghee Thean, Lim; Y. Chua, Soo (International Journal of Economics, Management and Accounting, 2022)
The persistent fish trade deficit of Malaysia may reflect the losing competitiveness of the sector. This study applies Revealed Comparative Advantage (RCA), Relative Trade Advantage (RTA), Revealed Competitiveness (RC) and Constant Market Share Competitiveness (CMSC) indices to assess the Malaysian fish export competitiveness against its five prominent ASEAN destinations (i.e., Singapore, Vietnam, Thailand, Indonesia, and Brunei) in 2009-2018. The study contributes to the literature by extending the scope of previous studies on the fishery sector competitiveness with a more advanced CMSC index that can identify potential markets for Malaysia, at the same time overcome the index number inconsistency problem under the traditional constant market share approach. Results reveal that Malaysia loses competitiveness in exporting fish. Also, from the result of CMSC analysis, Malaysia shows the least competitive fish export in Singapore but the most competitive in Thailand among the fish export destinations. Malaysia should venture more into downstream processing to add value to its fishery products and thus improve export. It is recommended that Malaysia concentrates more on Thailand, Vietnam, Indonesia, and Brunei markets where Malaysia enjoys a positive competitive effect besides further exploring other international markets for revitalizing Malaysian fish export.